2021
DOI: 10.3390/su13041626
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Work Engagement on Future Occupational Rankings, Wages, Unemployment, and Disability Pensions—A Register-Based Study of a Representative Sample of Finnish Employees

Abstract: Despite ample interest in the potential consequences of work engagement over the last two decades, the question of whether work engagement predicts proximal and more distal career-related outcomes has gained surprisingly little attention. Using Conservation of Resources (COR) theory and a sustainable careers framework, the aim of this study was to investigate whether work engagement predicts register-based outcomes of wages, moves in occupational rankings, unemployment, and disability pensions. We used nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…When employees feel vigorous and enthusiastic while working, they thrive and continuously develop themselves (Bakker and Schaufeli, 2008) – which contributes to career satisfaction. In a recent study, Hakanen et al. (2021) showed that work engagement also has important implications for objective career success.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When employees feel vigorous and enthusiastic while working, they thrive and continuously develop themselves (Bakker and Schaufeli, 2008) – which contributes to career satisfaction. In a recent study, Hakanen et al. (2021) showed that work engagement also has important implications for objective career success.…”
mentioning
confidence: 99%
“…When employees feel vigorous and enthusiastic while working, they thrive and continuously develop themselves (Bakker and Schaufeli, 2008) which contributes to career satisfaction. In a recent study, Hakanen et al (2021) showed that work engagement also has important implications for objective career success. The authors found that work engagement had a positive impact on future wages and the probability of rising in occupational rankings and a negative impact on future unemployment and disability pensions.…”
mentioning
confidence: 99%
“…Work engagement, as an energetic resource that employees may possess, should be a key priority in organizations, as it can increase life satisfaction and can prevent employees from psychological distress, depression, anxiety, sickness absenteeism, and burnout [23][24][25][26]. Furthermore, work engagement has been associated with healthy cardiac autonomic activity and a low likelihood of disability pensions [27,28]. Notably, high levels of work engagement have also been associated with increased short-term psychological distress and with decreased psychological stress over time [29].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, high levels of work engagement have also been associated with increased short-term psychological distress and with decreased psychological stress over time [ 29 ]. At the societal level, work engagement predicts less unemployment in the general population [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the fact that there is a growing academic interest in issues related to disability, sustainability, and employment ( [52][53][54][55][56][57][58][59][60], among others), as Ref. [32] mentioned, there is still limited information about workers with disabilities in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%